2012
DOI: 10.1016/j.jtos.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Neovascularization and the Utility of Topical VEGF Inhibition: Ranibizumab (Lucentis) Vs Bevacizumab (Avastin)

Abstract: Corneal avascularity is necessary for the preservation of optimal vision. The cornea maintains a dynamic balance between pro- and antiangiogenic factors that allows it to remain avascular under normal homeostatic conditions; however, corneal avascularity can be compromised by pathologic conditions that negate the cornea’s “angiogenic privilege.” The clinical relevance of corneal neovascularization has long been recognized, but management of this condition has been hindered by a lack of safe and effective thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
130
0
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 226 publications
0
130
0
17
Order By: Relevance
“…Steroids have been shown to have an inhibitory effect on vessel caliber in a chorioallantoic membrane model (McKay et al, 2008) and in a clinical study in patients with diabetic macular edema (Wickremasinghe et al, 2008), indicating an inhibitory effect of steroids on inflammatory cytokines inducing vessel expansion. The ability of anti-VEGF treatment to reduce mature vessel caliber has been demonstrated after topical instillation of bevacizumab in clinical studies König et al, 2009;Stevenson et al, 2012), an effect likely arising from blocking the permeability properties of VEGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroids have been shown to have an inhibitory effect on vessel caliber in a chorioallantoic membrane model (McKay et al, 2008) and in a clinical study in patients with diabetic macular edema (Wickremasinghe et al, 2008), indicating an inhibitory effect of steroids on inflammatory cytokines inducing vessel expansion. The ability of anti-VEGF treatment to reduce mature vessel caliber has been demonstrated after topical instillation of bevacizumab in clinical studies König et al, 2009;Stevenson et al, 2012), an effect likely arising from blocking the permeability properties of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the penetration of topically instilled dexamethasone into the cornea is known from clinical experience and earlier experimental studies (Bessonova et al, 2011;Hoffart et al, 2010;Hos et al, 2011). Topical anti-VEGF antibodies have similarly shown good penetration into the cornea, particularly after local disruption of the epithelial barrier and induction of inflammation and angiogenesis (Rocher et al, 2011;Stevenson et al, 2012;Yoeruek et al, 2008). In the present study, RT-PCR also revealed a significant effect on many cytokines belonging to inflammatory and angiogenic pathways as early as 24h, indicating the rapid effect of the topical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Alhammami et al [17] concluded that subconjunctival Bevacizumab is of benefit in cases of recurrent pterygium. The subconjunctival injection carries the potential risk of systemic complications such as gastrointestinal perforation, hypertension, arteriolar hemorrhage, impaired wound healing, bleeding, endophthalmitis, and arterial thromboembolic events Therefore, it has been suggested that topical instillation is the best route of Bevacizumab administration because it provides both safety and efficacy [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Alhammami et al [17] concluded that subconjunctival Bevacizumab is of benefit in cases of recurrent pterygium. The subconjunctival injection carries the potential risk of systemic complications such as gastrointestinal perforation, hypertension, arteriolar hemorrhage, impaired wound healing, bleeding, endophthalmitis, and arterial thromboembolic events Therefore, it has been suggested that topical instillation is the best route of Bevacizumab administration because it provides both safety and efficacy [18,19].The dose of topical bevacizumab was debated by many authors. An in vitro study conducted by Park et al [20] found that both metabolic activity and viability of primary and recurrent pterygium human Tenon fibroblasts (HTF's) are inhibited by bevacizumab in a dose-dependent manner, especially at concentrations greater than 7.5 mg/ml.…”
mentioning
confidence: 99%
“…55,56 Yapılan çalışmalarda ranibizumab'ın bevacizumab ile benzer etkinlikleri olduğu saptanmış olmakla beraber bir çalışmada topikal uygulamada ranibizumabın daha başarılı olduğu belirtilmiştir. 57 Etkinlik farkları muhtemelen moleküllerin büyüklükleri ve korneadan geçebilme özelliklerinden kaynaklanmaktadır.…”
Section: Anti-vasküler Endotelyal Büyüme Faktörü Antikorlarıunclassified